(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
Factoring, also known in Brazil as mercantile or commercial development, is a company that provides advisory services, anticipation of non-financial resources and purchase of credits, with predated checks or promissory notes originating exclusively from sales on credit. The objective of this research was to verify the period of the year in which industrial companies in the municipality of Presidente Getúlio, in Santa Catarina, have the greatest need to use the services provided by commercial development companies. The branch of activity studied was the industry area, where 177 questionnaires were applied, with 32 open and closed questions. The questionnaires were collected between August 30, 2012 and October 2, 2012. They were analyzed quantitatively and qualitatively. The results indicated that 72% of the participating companies use the services provided by commercial development companies every month of the year, 19% only from October to December, and 9% seek factoring companies only from January to March. . Inadequate management can lead to serious financial problems, effectively contributing to a situation of insolvency. It was found that the industrial companies of the municipality of Presidente Getúlio seek factoring services due to the fact that they do not have an effective administration, due to the organizational culture and also to the lack of financial resources.